ANALISIS SISTEM INFORMASI AKUNTANSI SIKLUS PENGGAJIAN PADA USAHA MEBEL AYU - Kabila, Nasywa A. S.; Ode, Fandi; Labiru, Dea; Maulia, Afril; Masihuwey, Rusdi H.; Denis E. S., Seinena; Sallatalohy, Nurul Salma; Uniplaita, Priska Ance; Huwat, Fahrul Israndi (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2023)
The purpose of this study was to analyze the accounting information system of the payroll cycle process in the Ayu Furniture industry. Data collected by interview, observation and documentation techniques. Observation and documentation techniques are directly carried out at the research location in the Ayu Furniture industry. Analysis carried out by the method (PIECES) Performance, Information, Economy, Control, and Efficiency. The research approach uses descriptive qualitative, namely by describing the payroll accounting information system that exists in the company which includes activities in the payroll system, related functions, documents used, accounting records used, network procedures that make up the system and internal control system. The results showed that the payroll process in the Ayu Furniture industry uses a manual system, this can lead to potential fraud or negligence at the stage of attendance and submission of employee salaries, although the system has been running smoothly and effectively in terms of service, performance, information and economy.